A Comparison of the Effects of Vitamin E and Vitamin B1 on the Severity and Duration of Pain in Primary Dysmenorrhea - Sara Nayeban; Farzaneh Jafarnejad; Samira Nayeban; Arash Sefidgaran (Mashhad University of Medical Sciences, 2014)
Background and aim: Primary dysmenorrhea is defined as painful menstruation in the absence of any confirmed pelvic disease. Its incidence has been estimated between 50-90% in different communities. Non-steroidal anti-inflammatory drugs (NSAIDs) and contraceptives are usually prescribed for the treatment of primary dysmenorrhea; however, they cause several specific complications. Due to the importance of this issue, some studies have been performed on medications with fewer side effects. This study aimed to compare the therapeutic effects of vitamin E and B1 on pain severity and duration in primary dysmenorrhea. Materials and Methods: This randomized clinical trial was conducted on 90 female students of Ferdowsi University of Mashhad, Iran, who met the inclusion criteria. At first, the participants, whose pain score of Visual Analogue Scale (VAS) was more than 40 during their three last menstrual cycles, were included and randomly assigned to two groups. The treatment was started by administrating vitamin B1 100mg/day for the first group (vitamin B1 group) and vitamin E 400unit/day for the second group (vitamin E group). Finally, two groups were compared in terms of the severity and duration of pain in dysmenorrhea. Results: The mean age of the participants was 22.97±3.23 years. There was a significant difference between pre- and post-treatment periods in terms of pain severity (PConclusion: It is recommended that vitamin E and B1 could be used interchangeably for treatment of primary dysmenorrhea.